Material Properties Extraction of Mango (Mangifera indica) Leaves at Ka-Band Using a Waveguide Measurement System - Arisesa, Hana; Idrus, Sevia Mahdaliza; Iqbal, Farabi; Abdullah, M.F.L; Wijayanto, Yusuf Nur; Adhi, Purwoko (Communications in Science and Technology, 2025)
This study investigates the material properties (permittivity, dissipation factor, and conductivity) of mango leaves (Mangifera indica) over the 26–40 GHz Ka-band frequency based on a waveguide measurement system with a vector network analyzer instrument to capture the data. The data analysis employs the Nicolson-Ross-Weir method to extract material properties. The result reveals that the real part of permittivity decreases from about 11.0 to 5.0 with increasing frequency. Meanwhile, the imaginary part of permittivity remains low and stable, suggesting minimal absorption losses. The dissipation factor is consistently below 0.05 along the band. Effective conductivity ranges from 0.2 to 0.6 S/m, with a slight increase at higher frequencies. These findings suggest that at Ka‐band frequency, signal degradation through mango foliage is primarily driven by dispersion and scattering rather than strong dielectric absorption. The results provide essential information for improving foliage attenuation models and designing 5G and 6G communication systems in tropical regions. This study provides a reliable Ka-band dielectric dataset for mango leaves that improves the accuracy of tropical foliage-attenuation models and supports more robust 5G/6G link design and deployment in vegetation-dense environments.